Analisis Permasalahan Bentuk Konstruksi Rangka Atap di Indonesia - Christophorus Koesmartadi; Mohhamad Kusyanto; B. Resti Nurhayati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: Analysis of The Problems in the Form of Roof Truss Construction in Indonesia The Nusantara archipelago has various architectural forms, such as traditional houses with various roof shapes. These roof shapes consist of various forms of roof support frame construction. Problems arose when the Dutch came and brought the concept of truss construction. This concept was massively applied throughout the Nusantara archipelago, even making the architectural construction learning system in Indonesia use methods developed by the Dutch, making it hard to align with construction in the archipelago. This study uses a qualitative method with data collection through observation, interviews, and documentation studies. The analysis was carried out by identifying and comparing traditional houses' roof frame construction supports and their roof slabs with houses with horse-horse construction from the Netherlands to gain knowledge of the problems in the roof construction of both. The findings of this study are that the roof shape and support construction are one package as an interaction between the shape and support construction. These diverse forms also give birth to various roof support frame construction forms. However, the influence of the Dutch horse-horse construction has made experts more inclined to use the Dutch hanging horse concept rather than developing roof support frame construction that has been proven to be integrated with the roof shape. Nowadays, the hanging truss concept has many applications in the construction of traditional houses, which is considered less suitable.